TABOO WORDS FOUND IN CRANK 2: HIGH VOLTAGE - Dewa Ngakan Putu Bayu Miarta; I Nyoman Muliana; I Made Astu Mahayana (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2019)
Taboo words are a proscription of behaviour which affects people’s social life. The words and expressions classified as taboo are commonly used to describe sex, our bodies and their functions, and also to insult other people. This article analyzes the kinds and the functions of taboo words found in Crank 2: High Voltage movie. The method used in this research is qualitative research. To analyze the problems of this research, it is applied the theory of taboo words by Jay and the functions of taboo by Wardaugh. From the analysis, it is found seven kinds of taboo word occurred in the movie. They are profanity, obscenity, vulgarity, slang, epithets, insult and slurs, and scatology. Furthermore, the function analysis found in this research includes: to draw attention to oneself, to show contempt, to be provocative, and to mock authority.